PEMBENTUKAN PERATURAN DESA DALAM KONTEKS KETATANEGARAAN INDONESIA - NURAINI, NURAINI (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
Law Number 32 Year 2004 About local governance, that further arrangements regarding the village, including the problem of the formation of the rules of the village (the village Regulations) arranged in the form of Regulatory regions of the County. The type of Research used in this study using normative legal research using